EFFECTIVENESS OF SETTLEMENT OF NON-INDIGENOUS CREDIT LOANS WITH NON-LITIGATION COLLATERAL RIGHTS - A.A. Putu Yudha Maha Putra; I Made Arjaya; I Ketut Kasta Arya Wijaya (Sean Institute, 2023)
The Village Credit Institution (known as LPD) is a special financial institution established by Traditional Villages in Bali. In solving the problems encountered, the solution refers to Pararem regarding LPD in each Traditional Village. This study analyzes the Procedures for Granting Credit for the Settlement of Unpaid Loans for Customers Outside Traditional Villages with Mortgage Guarantees through Non-Litigation Channels. This study uses empirical legal research methods on the LPD in the Kerobokan Traditional Village. The Kerobokan Traditional Village LPD disburses credit based on the procedural provisions for granting credit as stipulated in the Pararem Desa Adat regarding LPD. The procedure for granting credit at the Kerobokan LPD is carried out by filling in a credit application form, bringing personal identification, and collateral that is pledged as collateral, and known to the husband and wife. Loan applications are analyzed using the 6C plus 1I principles, namely character, ability, capital, guaranteed business prospects, economic conditions, cash flow, and instinct. The takeover of collateral is carried out if the debtors do not carry the obligation at loan agreements. Based on Pararem it is explained that if a credit problem occurs, initial handling will be given an oral notification, then notification of a warning letter, and by carrying out lengthy coaching to the debtor. Credit settlement is carried out by taking over collateral and auctioning or helping to sell the credit guarantee to resolve the problem of bad credit so that the LPD does not experience losses due to debtor disobedience in the credit agreement at the LPD.